Web-oriented encyclopedic edition as a tool for dissemination of verified knowledge in the field of education - Olha P. Pinchuk; Liliia A. Luparenko (Academy of Cognitive and Natural Sciences, 2023)
The article deals with the problem of creating a Ukrainian web-oriented encyclopedia to support terminology of education and psychology. The project is designed by the Institute for Digitization of Education of the National Academy of Educational Sciences of Ukraine (IDE NAES of Ukraine). The initial stages of the "Ukrainian Electronic Encyclopedia of Education" implementation procedure were presented. The structure of the encyclopedia website, its software platform, functionality, a search toolkit, articles typology, thematic sections, authors` team, and target audience were described. The authors analyzed the principal reference resources regarding encyclopedic editions (Corpus of Ukrainian Encyclopedias, Electronic library of the NAES of Ukraine, V. O. Sukhomlynskyi State Scientific and Pedagogical Library of Ukraine, and ScienceDirect). A review of international scientific publications was carried out. The problem of open use the verified, scientific, and succinctly presented content is revealed. It is emphasized the need for technical and technological implementation of the following capabilities: content uploading, editing, and enhancing support; coordinated work of the international scientific authors' team; open access anytime and anywhere for many users; search functions by various parameters on the site, etc.